Alcoholic monoterpenes found in essential oil of aromatic spices reduce allergic inflammation by the modulation of inflammatory cytokines. Issue 12 (18th June 2019) - Pina, Lícia T. S.; Ferro, Jamylle N. S.; Rabelo, Thallita K.; Oliveira, Marlange A.; Scotti, Luciana; Scotti, Marcus Tullius; Walker, Cristiani Isabel Bandero; Barreto, Emiliano O.; Quintans Júnior, Lucindo J.; Guimarães, Adriana G.
Abstract: Allergic inflammation is a response of the body against pathogens by cytokine release and leucocyte recruitment. Recently, there was an increase in morbimortality associated with allergic inflammation, especially asthma. The treatment has many adverse effects, requiring the search for new therapies. Monoterpenes are natural products with anti-inflammatory activity demonstrated in several studies and can be an option to inflammation management. Thus, we investigated the effects of citronellol, α-terpineol and carvacrol on allergic inflammation. The model of asthma was established by OVA induction in male Swiss mice. The monoterpenes were administered (25, 50 or 100 mg/kg, i.p.) 1 h before induction. After 24hs, the animals were sacrificed to leucocytes and TNF-α quantification. Monoterpenes significantly decrease leucocyte migration and TNF-α levels, possibly by modulation of COX, PGE2 and H1 receptor, as demonstrated by molecular docking. These findings indicate that alcoholic monoterpenes can be an alternative for treatment of allergic inflammation and asthma. Abstract :